Does prenatal methamphetamine exposure affect the drug-seeking behavior of adult male rats? - Slamberová, Romana; Schutová, Barbora; Hrubá, Lenka; Pometlová, Marie (Behavioural brain research, 2011)
Methamphetamine (MA) is one of the most frequently used illicit drugs worldwide and also one of the most common drugs abused by pregnant women. Repeated administration of psychostimulants induces behavioral sensitization in response to treatment of the same or related drugs in rodents. The effect of prenatal MA exposure on sensitivity to drugs in adulthood is not yet fully determined. Because our most recent studies demonstrated that prenatal MA (5mg/kg) exposure makes adult rats more sensitive to acute injection of the same drug, we were interested whether the increased sensitivity corresponds with the increased drug-seeking behavior. The aim of the present study was to examine the effect of prenatal MA exposure on drug-seeking behavior of adult male rats tested in the conditioned place preference (CPP). The following psychostimulant drugs were used as a challenge in adulthood: MA (5mg/kg), amphetamine (5mg/kg) and cocaine (10mg/kg). All psychostimulant drugs induced increased drug-seeking behavior in adult male rats. However, while MA and amphetamine-induced increase in drug-seeking behavior did not differ based on the prenatal drug exposure, prenatally MA-exposed rats displayed tolerance effect to cocaine in adulthood. In addition, prenatally MA-exposed rats had decreased weight gain after administration of MA or amphetamine, while the weight of prenatally MA-exposed rats stayed unchanged after cocaine administration. Defecation was increased by all the drugs (MA, amphetamine and cocaine), while only amphetamine increased the tail temperature. In conclusion, our results did not confirm our hypothesis that prenatal MA exposure increases drug-seeking behavior in adulthood in the CPP test.
Keywords: potkani Wistar; krysa rodu Rattus; analýza rozptylu; Amphetamine; Disease Models, Animal; modely nemocí na zvířatech; operantní podmiňování; zpožděný efekt prenatální expozice; těhotenství; Rats; Substance-Related Disorders; tělesná hmotnost; Conditioning, Operant; mužské pohlaví; Female; Prenatal Exposure Delayed Effects; Rats, Wistar; Body Weight; Male; Analysis of Variance; ženské pohlaví; Pregnancy; poruchy spojené s užíváním psychoaktivních látek; Animals; Methamphetamine; Dopamine Agents; dopaminové látky; zvířata; amfetamin; Cocaine; methamfetamin; kokain